THE SCHAFFER FORMULA CAN’T PREDICT LIVEWEIGHT IN BACK BELLY SHEEP - Pedro Colorado-Garcia; José Luis Ponce-Covarrubias; Roberto Carlos Barrientos-Medina; Claudia V. Zaragoza-Vera; Maritza Zaragoza-Vera; Oswaldo M. Torres-Chable; Alfonso Juventino Chay Canul (Tropical and Subtropical Agroecosystems)
Background. Schaeffer's formula has been promoted as an alternative to animal weighting in recent years. However, no studies evaluating the Schaeffer formula in the Black Belly hair sheep breed have been developed. Objective. To evaluate Schaeffer's formula for predicting body weight in male and female Black Belly sheep reared under tropical conditions. Methodology. Body weight (BW, kg), thoracic circumference (TC, cm) and body length (BL, cm) were recorded in 120 Black Belly lambs (60 females and 60 males). The lambs were clinically healthy and aged between 6 and 8 months. Schaeffer's formula for calculating BW was BW (kg) = (BL × TC2)/10838. First, the distributions of the values were examined by means of a histogram showing both sets of values simultaneously. The medians of each set were then obtained and statistically compared using the Wilcoxon signed-rank test to test the null hypothesis of no difference between the two sets of measurements considered. Results. In the present study it was observed that Shaeffer's formula underestimated BW in Black Belly sheep (P<0.05) at about 5.84 kg. This weight represents about 20.40% of the observed mean BW. The underestimation was also much greater than expected in males at approximately 6.88 kg, this weight represents approximately 22.40% of the observed mean BW in males. However, for females the difference was 4.09 kg. This weight represents approximately 15.40% of the observed mean BW for females. Implications. Caution should be exercised in using the Schaffer formula for estimating liveweight in black belly sheep, or some adjustment to this equation should be evaluated to increase its precision and accuracy for predicting liveweight in hair sheep breeds. Conclusion. Under the conditions in which the present study was carried out, it was concluded that Shaeffer's formula underestimated BW in Black Belly sheep. The estimated BW differed from the observed BW (P<0.05), and this parameter was underestimated much more than expected in males than in females, showing that this formula is not accurate in estimating BW in male and female Black Belly sheep. As a result, estimates should be treated with caution. There is a need to develop improved prediction equations for adequate estimation of BW of male and female Black Belly sheep.